Pramoedya Ananta Toer's Novels on Independence Revolution from the Perspective of Journalistic Hegemony: (Novel Revolusi Kemerdekaan karya Pramoedya Ananta Toer dalam Perspektif Hegemoni Jurnalistik) (Malay Literature, 2021)
The journalistic hegemony conceptual framework is an approach in the study of literary works in all genres. This framework functions on the principle that a literary work is a creative medium that comprises facts, data and reality that is fictionalized for the purpose of spreading information to its readers, similar to that of conventional media. Based on documentary research and content analysis, this study proves that Pramoedya Ananta Toer's novels on the theme of the Indonesian National Revolution (1945-1949)-Di Tepi Kali Bekasi (1951), Keluarga Gerilya (1955), Sekali Peristiwa di Banten Selatan (1963) and Larasati (2003)-are creative media intended to raise awareness among the Javanese marginal class. The focus of this study is to prove that Pramoedya Ananta Toer's novels are creative media designed to create hegemony and mental awareness, both intellectually and ideologically, in the social class he represents. The journalistic hegemony conceptual framework is based on the principle of comparative hegemony by Antonio Gramsci and the communication theory. The hypodermic needle theory places these novels on revolution by Pramoedya Ananta Toer as having the function of spreading information creatively in order to raise awareness and subsequently free the marginal class of false consciousness nurtured by the traditional bureaucratic elites and Dutch colonizers in Java.Keywords: Journalistic hegemony, intellectuality, ideology, Hypodermic Needle Theory, marginal class